1993
DOI: 10.1080/14640749308401088
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Learning during Filial Imprinting: Evidence from Transfer of Training Studies

Abstract: Chicks were first imprinted by exposing them to a moving training stimulus, B or C, that was projected onto a screen at one end of an experimental cabinet. Subsequently, subjects selectively approached the stimulus to which they had been exposed. On the following day, the chicks were placed into a chilled experimental cabinet (15°C) and received trials on which two stimuli (A and B) were projected onto screens located at opposite ends of the cabinet. If the subject approached Stimulus A, a stream of warm air w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Chamizo and Mackintosh (1989;see also Trobalon, Sansa, Chamizo, & Mackintosh, 1991) have found that separate nonreinforced exposure to each ofthe relevant maze arms can facilitate subsequent discrimination learning in which rats are rewarded for choosing one arm rather than the other. Studies of the domestic chick (e.g., Honey, Horn, & Bateson, 1993) have shown that discrimination between two cues is enhanced by prior training designed to allow imprinting to each ofthe cues. In studies offlavor-aversion learning, it has been shown that an aversion conditioned to one flavor will generalize less well to another when the animals have had prior experience of these flavors.…”
Section: The Phenomenonmentioning
confidence: 99%
“…Chamizo and Mackintosh (1989;see also Trobalon, Sansa, Chamizo, & Mackintosh, 1991) have found that separate nonreinforced exposure to each ofthe relevant maze arms can facilitate subsequent discrimination learning in which rats are rewarded for choosing one arm rather than the other. Studies of the domestic chick (e.g., Honey, Horn, & Bateson, 1993) have shown that discrimination between two cues is enhanced by prior training designed to allow imprinting to each ofthe cues. In studies offlavor-aversion learning, it has been shown that an aversion conditioned to one flavor will generalize less well to another when the animals have had prior experience of these flavors.…”
Section: The Phenomenonmentioning
confidence: 99%
“…In all experiments, generalization was greater when the auditory stimuli were matched for familiarity (either both stimuli were familiar or both stimuli were novel) than when their familiarity was mixed (one was familiar, the other novel); that is, generalization occurred along a dimension of stimulus familiarity (cf. Best & Batson, 1977 ; Gaffan, 1974 ; Honey, 1990 ; Honey et al, 1993 ; Robinson et al, 2010 ). We saw also that familiarity-based generalization did not seem to be the result of sensory preconditioning occurring in Group CT (cf.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of animals’ ability to discriminate novel from familiar stimuli is central to our understanding of recognition memory (e.g., Mackintosh, 1987 ; Mandler, 1980 ) and has implications for our understanding of stimulus representation (e.g., Gaffan, 1974 ; Honey, 1990 ; Honey, Horn, & Bateson, 1993 ; McLaren & Mackintosh, 2002 ). Much understanding of animals’ novelty/familiarity discrimination comes from studies of rodents’ spontaneous object recognition (e.g., Olarte-Sanchez, Amin, Warburton, & Aggleton, 2015 ; Whitt & Robinson, 2013 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation of these findings could entail a dissociation of separate elements involved in the formation of imprinting memory (e.g., elements associated with the discrimination of the imprinting stimulus from other stimuli may be dissociated from those required for approach behavior during testing; see Honey, Horn, & Bateson, 1993). Andrew (1997) has proposed that memory requires hemispheric interaction so that linkages are established between different trace fragments.…”
Section: Discussionmentioning
confidence: 99%